The Effect of Written Examinations on Attitude and Achievement in College Freshman Mathematics at Alvin Community College - Douthitt, Cameron B. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This study consisted of two sections of Finite Mathematics at Alvin Community College, one with 26 students and another with 21 students. The teaching strategy for both sections was basically the same with a variety of teaching aids being used in both. The comparison group was evaluated by the traditional written examination, weekly homework assignments, and some chalkboard work once a week. The experimental group was evaluated subjectively from each performance at the chalkboard and from exercises turned in at the conclusion of each class, as well as from weekly homework assignments. No significant difference in attitude towards mathematics or achievement in mathematics was found between the two groups. However, mean scores on both the Aiken-Dreger Mathematics Attitude Test (revised) and the Alvin Community College Mathematics Placement Test were higher for the experimental group. (MN)
Sponsoring Agency: Alvin Community Coll., TX.
ERIC Note: Contains light and broken type.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement; Attitudes; College Freshmen; College Mathematics; Educational Research; Evaluation Methods; Higher Education; Mathematics Education; Testing; Tests; Written Tests; Reports, Research